PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX TAHUN 2011-2015 - admin, Vedia Suitasari B11112012 (Jurnal Manajemen Update, 2016)
The study purpose is to examine the effect of Good Corporate Governance on company value. The sampling technique used in this study is purposive sampling with research sample consisted of 24 companies within a period of five years so the observation numbers of 120 observational data associated with six variables. There are five independent variables: board of directors, independent commissioner, managerial ownership, institutional ownership, audit committee, quality audit, and one dependent variable is company value as measured by Tobinâ€™s Q. The data analysis technique used in this sudy is multiple linear regression. Classical assumption including normality test, linearity test, multicolinearity test, heteroscedasticity test, and autocorrelation test. The other hand, hypothesis testing using t-statistics and f-statistics, and the last determination test. The result in this study showed (1)Board of directors variable has not influence on company value, (2)Independent commissioner has influence influence on company value, (3)managerial ownership has not influence on company value, (4) institutional ownership has not influence on company value, (5) audit committee has influence influence on company value, (6) quality audit has influence influence on company value. Â  Keywords: Good Corporate Governance, Board Of Directors, Independent Commissioner, Managerial Ownership, Institutional Ownership, Audit Committee, Quality Audit, and Company Value Â